THE PREVALENCE OF OBESITY AND OVERWEIGHT AND FLEXIBILITY IN TEENS LEVELS OF 14 TO 18 YEARS (Fiep Bulletin - online, 2013)
Society today lives with the problems of obesity and overweight, especially with teens by their habits of contemporary life. From this observation, set up this cross sectional study was carried-analytical in town and Empress - MA and had a population sample of 118 adolescents aged 14 to 18 years. The aim was to relate the influence of body weight through the juvenile body mass index in the posterior muscle chain flexibility of the back and legs, through your evaluation by test sit-and-reach. According to data obtained body mass index, there was a prevalence of normal weight: 98 (83%), followed by overweight: 15 (12.8%). In the classification by gender, the prevalence of normal weight: Male 39 (73.6%) female and 59 (93.0%) and overweight: male 12 (22.6%) and females (4.5%). Assessing the flexibility, the present study demonstrated that most teenagers fits the classification of "reasonable" 34 (28.8%), while 24 (20.3%) in classification "very good" and 22 others (18, 7%) in classification "very weak" and yet, 19 (16.1%) are in the classification of weak and another 19 (16.1%) were classified as "good". The relationship between BMI and the assessed level of flexibility not found any evidence was proportional or inversely proportional between these variants. Thus, the results showed no significant influence related to body mass index with levels of flexibility, since adolescents with normal weight and overweight, achieved results in sit and reach test statistically close.
Keywords: adolescence; flexibility; IMC.